2020
DOI: 10.4314/gmj.v54i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of chronic illness among older patients attending a university hospital in Nigeria

Abstract: Background: The rising burden of chronic diseases has attracted the attention of public health researchers and policymakers worldwide. Objectives: To assess the demographic, morbidity and outcome patterns of chronic illness among the older patients at Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria. Design: Retrospective study Setting: Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria. Participants: Seven hundred and eighty-eight (78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A multi-country study on health data reporting in PHCs in five LMICs including Nigeria found that data was primarily collected in outpatient care, antenatal care, immunization, family planning, HIV and tuberculosis services only [ 39 ]. Although older adults vary greatly in terms of health status, the majority of them have at least one chronic condition and are prone to other age-related diseases such that the current data reporting system in the PHCs will exclude them from care [ 40 , 41 ]. In comparison to high-income countries, data on aging and the well-being of older people in Low- or Middle- Income Countries (LMICs) are insufficient and might not be fully representative of the aging populations in the countries flagging the need to prioritize research for informed decision-making [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multi-country study on health data reporting in PHCs in five LMICs including Nigeria found that data was primarily collected in outpatient care, antenatal care, immunization, family planning, HIV and tuberculosis services only [ 39 ]. Although older adults vary greatly in terms of health status, the majority of them have at least one chronic condition and are prone to other age-related diseases such that the current data reporting system in the PHCs will exclude them from care [ 40 , 41 ]. In comparison to high-income countries, data on aging and the well-being of older people in Low- or Middle- Income Countries (LMICs) are insufficient and might not be fully representative of the aging populations in the countries flagging the need to prioritize research for informed decision-making [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multi-country study on health data reporting in PHCs in five LMICs including Nigeria found that data was primarily collected in outpatient care, antenatal care, immunization, family planning, HIV and tuberculosis services only [33]. Although older adults vary greatly in terms of health status, the majority of them have at least one chronic condition and are prone to other age-related diseases such that the current data reporting system in the PHCs will exclude them from care [34,35]. In comparison to high-income countries, data on aging and the well-being of older people in LMICs are insufficient and might not be fully representative of the aging populations in the countries flagging the need to prioritize research for informed decision-making [36].…”
Section: Discussionmentioning
confidence: 99%
“…Patients of persons living with chronic illnesses. According to a research paper on patterns of chronic illnesses conducted in Nigeria in 2020 [4], the percentage of chronic diseases in Nigeria is about 64.9% of the population. This was used as a proxy to estimate the population prevalence of chronic diseases given that the population of Nigeria is about 200 million [5].…”
Section: Sample Size Determinationmentioning
confidence: 99%